2020
DOI: 10.1097/sla.0000000000004339
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Duodeno-Jejunal Bypass Liner in Patients With Metabolic Syndrome

Abstract: Objective: The aim of this study was to compare the efficacy and safety of 12-month implantation of a duodeno-jejunal bypass liner (DJBL) with conventional medical care in patients with metabolic syndrome (MS). Summary Background Data: DJBL is an endoscopic device for treating obesity and related disorders. The persistence of favorable results after 6 months has not been tested in a controlled study. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…While Ruban and his colleagues ( 37 ) concluded a significant reduction in weight loss at 12 months, there was no significant difference in %TBWL observed between both groups at 24 months after the removal of DJBL. The other study by Caiazzo et al ( 39 ) also found no significant difference in observed BMI loss after the removal of DJBL.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…While Ruban and his colleagues ( 37 ) concluded a significant reduction in weight loss at 12 months, there was no significant difference in %TBWL observed between both groups at 24 months after the removal of DJBL. The other study by Caiazzo et al ( 39 ) also found no significant difference in observed BMI loss after the removal of DJBL.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, for the other cardiometabolic risk factors such as blood pressure, EFAs, total cholesterol, and LDL cholesterol, Laubner et al ( 40 ) and Glaysher et al ( 38 ) both showed significant decreases in the DJBL group vs. the SMT group. However, Caiazzo et al ( 39 ) found that there was no significant difference in BMI loss, HOMA2, blood pressure, HDL cholesterol and triglycerides after removal of DJBL. Additionally, with respect to cardiovascular risk profile, Koehestanie et al ( 41 ) found that DJBL intervention could possibly reduce the estimated 10-year coronary heart disease risk by 2 vs. 1% in the control group according to the UK Prospective Diabetes Study Risk Engine ( 42 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations